Motivational influence of virtual reality in physical therapy for children with cerebral palsy: a systematic review protocol - Huda Aliah Mohd Iqbal; Asfarina Zanudin; Nor Azlin Mohd Nordin (BMJ Open)
Introduction Emulating the vast inclusion of advanced technology in everyday practice, the medical world is no exception to its implementation, in particular, virtual reality (VR). Initially, its introduction as a therapy was accompanied by high aspirations and expectations for its growth and potential. Motivation is said to be the most associated benefit; although it is imperative to note that there exists a paucity of research that specifically quantifies its tangible impact on cerebral palsy (CP). There has yet to be a systematic review of the instruments used to precisely measure motivation and examine its association with the benefits of VR for children with cerebral palsy.Methods and analysis This review will evaluate comparative studies that used VR therapy as part of interventions for children with CP. Qualitative studies, single-case studies, systematic reviews, literature reviews and guideline audits will be excluded. This review will be conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA-P) guidelines. The methodological protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO). The following electronic databases will be used to access related studies published between January 2012 and December 2023: MEDLINE (via EBSCOhost), Web of Science, Scopus, PubMed and Cochrane. The Peer Review of Electronic Search Strategies checklist will be employed to develop database search strategies.Ethics and dissemination This review does not require ethical approval as it uses secondary data. The findings will be published in a scientific journal. We intend to contribute to the expansion of knowledge concerning the motivational implications of VR on children with CP.PROSPERO registration number International Prospective Register of Systematic Reviews (identification number CRD42023401079).